2013
DOI: 10.1111/all.12132
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents development of eosinophilic rhinosinusitis with nasal polyps in a mouse model

Abstract: Resveratrol may be useful for the prevention of eosinophilic CRSwNP. A key mechanism of its action is believed to be its anti-inflammatory effect, particularly on eosinophils, by inhibiting the lipoxygenase pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
(31 reference statements)
2
36
0
Order By: Relevance
“…Indeed, a large body of recent reports has verified the health-promoting bioactivity of RSV333435363738. As one of its many effects, RSV has been reported to have a therapeutic effect on nasal polyps639. However, the administration of RSV is limited by its very low aqueous solubility4041.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large body of recent reports has verified the health-promoting bioactivity of RSV333435363738. As one of its many effects, RSV has been reported to have a therapeutic effect on nasal polyps639. However, the administration of RSV is limited by its very low aqueous solubility4041.…”
Section: Discussionmentioning
confidence: 99%
“…Given our previous experience with a mouse model of eosinophilic CRS, we do not attribute the inadequate harvest to a technical problem. 19,20 We found that mechanical injury of the murine nasal mucosa exposed the bone and triggered neo-osteogenesis and formation of bony synechia (Fig. 2).…”
Section: Discussionmentioning
confidence: 91%
“…and ). Given our previous experience with a mouse model of eosinophilic CRS, we do not attribute the inadequate harvest to a technical problem …”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [41] explored the therapeutic effects of resveratrol in a mouse model of chronic rhinosinusitis with nasal polyps (CRSwNP) and the mechanism of action. Both eosinophilic infiltration and subepithelial fibrosis were significantly decreased by high-dose resveratrol; the potency of which was similar to that of triamcinolone acetonide.…”
Section: Discussionmentioning
confidence: 99%